Does Action Learning Promote Collaborative Leadership? - Joe Raelin (Academy of Management Learning & Education, 2006)
Given the need to unlock the capacity of everyone in the organization, interest in collaborative leadership is growing. But how is such a practice developed? The author proposes the use of action learning-in its original formulation, namely, through reflection on real-time work experience dealing with unfamiliar problems-as a gateway to collaborative leadership. Action learning is portrayed as growing in acceptance as a management education and learning approach that distills knowledge from a context to be used to provide learning to the practice as well as to the practitioner. The account demonstrates how the operating practices of collaborative leadership are directly affected by action learning and proposes that the two approaches are based on common principles.
Keywords: M10; M12; M53; O15; J28; L29; 650; Collaborative leadership; Action learning; Collective leadership; Shared leadership; Facilitation; Change agency; Leadership; Leadership development